Pengaruh Antrian Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Biznet Home Di Branch Kelapa Gading - Vicky Desna Adi Lelono; Resista Vikaliana (Jurnal Sains Sosio Humaniora, 2020)
The purpose of this research is to determine the effect of queue, service quality on customer satisfaction of Biznet Home in Kelapa Gading Branch partially and simultaneously. The population in this research is the customers of Biznet Home in the Jakarta Utara region. Total sample amount of this research is 32 respondents, which for the sampling here by using the Purposive Sampling technique. Data collected by using survey method with questionnaire instrument. For the data analysis method used by the researcher, is double regression analysis, t test (partial) and F test (simultaneous). From the result of this research shows that: (1) The effect of Queue positively affects the customer satisfaction, with tcount 3.912 > from ttable or 3.912>2.045 then H1 is accepted. (2) The Service Quality significantly affects the customer satisfaction, tcount 6.653 > from the ttable or 6.653 > 2.045 then H2 is accepted. From the result of those hypothesis test then the decision taken is simultaneously all of the independent variable has positive and significant effects on customer satisfaction.